Theoretical and experimental investigations of the Landau-Pomeranchuk-Migdal effect in amorphous and crystalline matter - Shul'ga, N.F.; Fomin, S.P. (Вопросы атомной науки и техники, 2003)
The brief review of theoretical investigations carried out in NSC KIPT on the problem of multiple scattering effect on radiation of high energy particles in matter is presented. The comparison of results of the theory with experimental data obtained recently on accelerators of SLAC and CERN at the study of the Landau-Pomeranchuk-Migdal effect in amorphous and crystalline matter is carried out.